CsICS gene overexpressed in sweet orange enhanced the resistance to Candidatus Liberibacter asiaticus - Rampim, Bruno Thomaz [UNESP]; Della Coletta-Filho, Helvécio; Freitas-Astúa, Juliana; Boscariol-Camargo, Raquel Luciana (FapUNIFESP (SciELO), 2025)
ABSTRACT Huanglongbing (HLB) is a severe disease affecting citrus worldwide, caused by Candidatus Liberibacter asiaticus (CLas). Transgenic plants overexpressing genes that confer resistance to CLas could serve as an effective strategy for controlling HLB. Transgenic citrus plants were previously developed to overexpress the Citrus sinensis (CsICS) (isochorismate synthase) gene, which is involved in salicylic acid (SA) biosynthesis and may activate systemic acquired resistance (SAR) to bacterial infection. This study evaluated the response of these plants to CLas infection. Transgenic sweet orange plants cv. Hamlin were challenged against CLas by grafting infected citrus buds, and infection was firstly detected at six months post-inoculation via quantitative polymerase chain reaction. From six to 30 months post-inoculation (mpi), CLas titer, symptom expression, and disease severity were assessed. Gene expression analysis was performed for C. sinensis, nonexpressor of PR genes 1 (CsPR1) and salicylic acid carboxyl methyltransferase (CsSAMT), which are associated with SAR and SA production. Plants of the events CsICS 4-4 and 6-11 exhibited infection rates of 7.7 and 6.6%, respectively, while CsICS 4-19 showed 28% infection, compared to 64% in wild-type plants. The CsICS 4-4 event demonstrated increased resistance and significantly lower bacterial concentrations (7.15 × 103 CLas per gram of tissue) compared to the wild type (1.77 × 106 CLas per gram of tissue) at 12 mpi. Notably, CsICS 4-4 plants lacked characteristic HLB symptoms. Gene expression analysis confirmed that CsICS gene expression was upregulated in transgenic plants regardless CLas infection. The transgenic events showed a significant response to CLas, with reduced symptom severity and fewer infected plants, highlighting their potential for HLB management.